Dosimetric analysis of ultrasound-guided high intensity focused ultrasound ablation for breast fibroadenomas: a retrospective study. (31st December 2022) - Zhang, Cai; Liang, Mengdi; Xia, Tiansong; Yin, Heng; Yang, Hongwei; Wang, Zhibiao; Zhang, Lian
Abstract: Objective: To investigate the factors influencing the sonication dosage and efficiency of ultrasound-guided high intensity focused ultrasound (USgHIFU) for breast fibroadenomas. Materials and Methods: Forty-nine patients with 78 breast fibroadenomas who underwent USgHIFU were retrospectively analyzed. The energy efficiency factor (EEF) was set as dependent variable, and the factors possibly influencing the sonication dosage, including age, body mass index (BMI), fibroadenoma size, distance from the shallow margin of the fibroadenoma to skin, distance from the deep margin of the fibroadenoma to pectoralis major, types of near field acoustic pathway, and Adler blood flow classification of ultrasound, were set as independent variables. The correlation between EEF and these independent variables were analyzed, and an optimal scaling regression model was established. Results: Fibroadenoma size, distance from the shallow margin of the fibroadenoma to skin and type of near field acoustic pathway had significant correlation with EEF ( p  < 0.05). An EEF (ŷ) dosimetry model of ŷ= −0.496X1  + 0.287X2  + 0.203X3 was established, in which X1 stands for size of fibroadenoma, X2 stands for the distance from shallow margin of the fibroadenoma to skin, and X3 stands for type of near field acoustic pathway. The predicted EEF value was significantly related to actual EEF ( R  = 0.698, p  = 0.000). Conclusions: Fibroadenoma size, distance from the shallow margin of the fibroadenoma to skin and type of near field acoustic pathway could be used as predictors to evaluate the dosage delivery of USgHIFU treatment for breast fibroadenomas.